2019
DOI: 10.1121/1.5132540
|View full text |Cite
|
Sign up to set email alerts
|

Noise exposure limit for children in recreational settings: Review of available evidence

Abstract: It is universally recognized that prolonged exposure to high levels of non-impulsive noise will lead to noise-induced hearing loss. These high levels of noise have traditionally been found in an occupational setting, but exposure to high levels of noise is increasingly common in recreational settings. There is currently no established acceptable risk of hearing loss in children. This review assumed that the most appropriate exposure limit for recreational noise exposure in children would be developed to protec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 72 publications
0
21
0
Order By: Relevance
“…Recent analyses have recommended that exposures to leisure noise not exceed an 8-h TWA level of 80 dB(A), with a 3 dB exchange [68,69] (Figure 1). Under these guidelines, a two-hour concert should be enjoyed at a level no greater than 86 dB(A), assuming that is the only dose of loud sound for the day.…”
Section: Preventing Noise-induced Hearing Lossmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent analyses have recommended that exposures to leisure noise not exceed an 8-h TWA level of 80 dB(A), with a 3 dB exchange [68,69] (Figure 1). Under these guidelines, a two-hour concert should be enjoyed at a level no greater than 86 dB(A), assuming that is the only dose of loud sound for the day.…”
Section: Preventing Noise-induced Hearing Lossmentioning
confidence: 99%
“…The U.S. National Institute for Occupational Safety and Health maximum time-weighted average (TWA) recommended exposure level (i.e., the NIOSH REL[14] in blue), and the U.S. Occupational Safety and Health Administration maximum TWA permitted exposure level (i.e., the OSHA PEL[16] in red), is plotted as a function of exposure duration. In addition, a recent recommendation for maximum TWA exposure levels for leisure noise[68,69] is plotted (in green), along with the U.S. Environmental Protection Agency (EPA) "effective quiet" level of ≤70 dB(A)[15].…”
mentioning
confidence: 99%
“…Recommendations from excellent peer-reviewed articles (e.g., Neitzel & Fligor, 2019;Roberts & Neitzel, 2019) and resources from authentic online content such as "It's a Noisy Planet: Protect Their Hearing" (Figg, 2018) and "Make Listening Safe Campaign" (World Health Organization, 2015) were utilized. Reviewing the entire narrated presentation and all the videos in one sitting required approximately 35-45 min.…”
Section: The Hear Projectmentioning
confidence: 99%
“…Therefore, during concerts, you should properly protect yourself by staying at a safe distance from the speakers to reduce the intensity of the sounds reaching the ears or wear ear protectors, both there and in clubs and during sporting events [17]. In addition, some researchers indicate a good effect of using headphones with sound isolation, because it has been shown that a higher background level in the environment leads to the use of higher levels of sound in the headphones [18].…”
Section: Prevention In the Child's Environmentmentioning
confidence: 99%